Pore-forming peptide of Entamoeba histolytica significance of positively charged amino acid residues for its mode of action - Jörg Andrä and Matthias Leipe (FEBS letters : for the rapid publication of short reports in biochemistry, biophysics, and molecular biology, 1994)
Amoebapore is a 77-residue pore-forming peptide from Entamoeba histolytica with antibacterial and cytolytic properties. It contains eight lysine residues and one histidine residue. Chemical modifications of amoebapore with various reagents affecting either both types of cationic residues or lysine and histidine residues separately resulted in virtually complete loss of pore-forming activity. The activity was restored by reversal of modifications. Whereas amoebapore was no longer capable of binding to phospholipid vesicles when its lysine residues were modified, the modification of the single histidine primarily affected oligomerization of the peptide upon membrane association.
Keywords: Amoebiasis; Amoebapore; Chemical modification; Membranolytic peptide; Pore formation; Entamoeba histolytica